Platelet Protease Activated Receptor 4 Receptor Genotype is associated with an increased Risk of Preterm Birth - Yusra Javaid, Abdul Aziz Shaikh, Mukesh Kumar, Tanveer Hussain, Jehangir Kazi, Samina (Pakistan Journal of Medical & Health Sciences, 2025)
Objective: To investigate the association between platelet protease-activated receptor 4 (PAR4) receptor genotypes and the risk of preterm birth. Study Design: Prospective cohort study. Place and Duration of Study: Liaquat University Hospital, Hyderabad and Department of Pathology, Liaquat University of Medical & Health Sciences, Jamshoro from 1st January 2022 to 30th June 2023. Methodology: A total number of 80 patients were enrolled. Blood of mothers was obtained on admission for genotyping the PAR4 gene. The principal outcome was preeclampsia or gestational hypertension at rate among patients having Thr/Thr genotype as against those with Ala/Thr and Ala/Ala genotypes. Severe preeclampsia was diagnosed before 37 weeks, and delivery before 37 wks due to preeclampsia and/or fetal growth restriction. Exposure was defined as the presence of the homozygous Thr/Thr genotype for the PAR4 Thr/Ala polymorphic site group 1. The comparator group consisted of non-homozygous women for the Thr allele, heterozygous group 2. Results: Preterm birth <37 weeks of Group I & Group II was 6 (15.0%) and 4 (14.0%), respectively. (p=0.499). Spontaneous preterm birth <37 weeks in Group I & Group II was 5 (12.5%) and 2 (5.0%), respectively. (p=0.235). Indicated preterm birth <37 weeks of Group I and Group II was 3 (7.5%) and 2 (5.0%), respectively. (p=0.644). Preeclampsia in Group I & Group II was 10 (25.0%) and 5 (12.5%), respectively. (p=0.152). Conclusion: The PAR4 receptor genotype as a significant risk variable for premature delivery, underscoring the need for genetic and mechanistic studies to develop targeted therapies. Integrating genetic screening into prenatal care could transform the management of high-risk pregnancies, improving maternal and neonatal outcomes. Keywords: Preterm birth, Platelet, PAR4, Preeclampsia, Genetics